Radiation Induced Sexual Dysfunction in Prostate Cancer Patients (Medical Forum Monthly, 2024)
Objective: To estimate the sexual dysfunction in biopsy proven prostate cancer patients and to identify the characteristics associated with sexual dysfunction in survivors of carcinoma prostate.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Oncology department of Nishtar Hospital, Multan from November 2023 to September 2024.Methods: This study aimed to determine the prevalence of sexual dysfunction (SD) in prostate cancer patients who had undergone pelvic radiotherapy. Data was collected using a structured questionnaire that included demographic information, treatment details and the International Index of Erectile Function (IIEF-5) questionnaire to assess the severity of sexual dysfunction (SD), ECOG performance status 0-1, intermediate and high risk cancer patients and duration post radiotherapy.Results: Among the 25 patients with SD, 4 (16.0%) were in the intermediate risk group, while 21 (84.0%) were in the high-risk group. Additionally, 6 patients (24.0%) with SD had diabetes, and 20 patients (80.0%) underwent concurrent hormonal therapy. Prior to radiation, 5 patients (20.0%) had SD, whereas 20 patients (80.0%) developed it six months after radiation, a statistically significant difference (p < 0.001).Conclusion: Sexual dysfunction is common among prostate cancer survivors, influenced by cancer treatment, risk stratification and age. Treatments like radiation can damage hormone-producing organs, leading to SD. Together, cancer treatment, risk stratification and aging contribute to the higher incidence of sexual dysfunction in prostate cancer patients.